Making the Writing and Research Connection with the I-Search Process: A How-To-Do-It Manual. - Glantz, Rochelle (Booklist, 2006)
Reviews the book “Making the Writing and Research Connection with the I-Search Process: A How-To-Do-It Manual,” by Julie I. Tallman, and Marilyn Z. Joyce.